Influence of Implant Inclination Associated With Mandibular Class I Removable Partial Denture - de Freitas Santos, Ciandrus Moraes [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Verri, Fellippo Ramos [UNESP]; Dantas de Moraes, Sandra Lucia [UNESP]; Falcon-Antenucci, Rosse Mary [UNESP] (Lippincott Williams & Wilkins, 2011)
The aim of this study was to use two-dimensional finite element method to evaluate the displacement and stress distribution transmitted by a distal extension removable partial denture (DERPD) associated with an implant placed at different inclinations (0, 5, 15, and 30 degrees) in the second molar region of the edentulous mandible ridge. Six hemimandibular models were created: model A, only with the presence of the natural tooth 33; model B, similar to model A, with the presence of a conventional DERPD replacing the missing teeth; model C, similar to the previous model, with a straight implant (0 degrees) in the distal region of the ridge, under the denture base; model D, similar to model C, with the implant angled at 5 degrees in the mesial direction; model E, similar to model C, with the implant angled at 15 degrees in the mesial direction; and model F, similar to ME, with the implant angled at 30 degrees in the mesial direction. The models were created with the use of the AutoCAD 2000 program (Autodesk, Inc, San Rafael, CA) and processed for finite element analysis by the ANSYS 8.0 program (Swanson Analysis Systems, Houston, PA). The force applied was vertical of 50 N on each cusp tip. The results showed that the introduction of the RPD overloaded the supporting structures of the RPD and that the introduction of the implant helped to relieve the stresses of the mucosa alveolar, cortical bone, and trabecular bone. The best stress distribution occurred in model D with the implant angled at 5 degrees. The use of an implant as a support decreased the displacement of alveolar mucosa for all inclinations simulated. The stress distribution transmitted by the DERPD to the supporting structures was improved by the use of straight or slightly inclined implants. According to the displacement analysis and von Mises stress, it could be expected that straight or slightly inclined implants do not represent biomechanical risks to use.
Keywords: Finite element analysis; dental implant; biomechanics; removable partial denture